Pelatihan Digital Marketing Guna Meningkatkan Penjualan UMKM Kecap Manis - Sigit Setiyanto; Taqy Muhammad Fadhil; Sigmawan Malikul Rahman (Jurnal Pengabdian Kepada Masyarakat Abdi Putra, 2024)
Sweet soy sauce MSMEs in Bantul Regency have great potential in supporting the local and national economy, but they have not yet optimally utilized digital technology for marketing. This study aims to improve the understanding and skills of sweet soy sauce MSMEs in Bantul in the field of digital marketing through comprehensive training. A qualitative method with a case study approach was used to explore the impact of the training on 15 MSMEs. The results showed an 80% increase in understanding and skills of MSMEs in utilizing digital platforms such as social media and e-commerce, as well as changes in the attitudes and behavior of MSME owners towards digital technology. A 30% increase in sales and market expansion were other positive impacts. However, understanding of online advertising still needs to be improved, with only 20% of MSMEs having a good understanding of it. This study recommends further training that is more specific and in-depth, as well as ongoing mentoring for MSMEs.